Endothelium, venous thromboembolism and ischaemic cardiovascular events - Gresele, Paolo; Momi, Stefania; Migliacci, Rino (Thrombosis and Haemostasis, 2010)
The association between venous thromboembolism and arterial thrombosis has emerged as consistent clinical observation in the last few years. While several experimental, epidemiological and pharmacologic studies support this association, the initial pathophysiological mechanism linking these two clinical conditions remains to be established. This review discusses the pathophysiological bases and a number of experimental and clinical observations suggesting that the common link between venous thromboembolism and arterial thrombosis is represented by a dysfunctional endothelium.
Keywords: Arterial thrombosis; atherothrombosis; venous thrombosis; endothelial cells; nitric oxide/NO